2022
DOI: 10.1097/j.pain.0000000000002580
|View full text |Cite
|
Sign up to set email alerts
|

Deoxy-sphingolipids, oxidative stress, and vitamin C correlate with qualitative and quantitative patterns of small fiber dysfunction and degeneration

Abstract: Defined by dysfunction or degeneration of Ad and C fibers, small fiber neuropathies (SFNs) entail a relevant health burden. In 50% of cases, the underlying cause cannot be identified or treated. In 100 individuals (70% female individuals; mean age: 44.8 years) with an idiopathic, skin biopsy-confirmed SFN, we characterized the symptomatic spectrum and measured markers of oxidative stress (vitamin C, selenium, and glutathione) and inflammation (transforming growth factor beta, tumor necrosis factor alpha), as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The third example is that Se is an important component of some enzymes in vivo, 56 and a biomarker of oxidative stress. 57 Previous findings revealed that Se mediated protective effects against docetaxel-induced adverse peripheral oxidative neurotoxicity and neuropathic pain in mice. 47 Yüksel et al reported that Se treatment significantly decreased fibromyalgia through modulating activities of TRPM2 and TRPV1 channels in rats.…”
Section: Discussionmentioning
confidence: 99%
“…The third example is that Se is an important component of some enzymes in vivo, 56 and a biomarker of oxidative stress. 57 Previous findings revealed that Se mediated protective effects against docetaxel-induced adverse peripheral oxidative neurotoxicity and neuropathic pain in mice. 47 Yüksel et al reported that Se treatment significantly decreased fibromyalgia through modulating activities of TRPM2 and TRPV1 channels in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is one of the most common causes of SFN, and neuropathic pain is commonly the first and leading symptom in patients with SFN, having the most relevant patient-reported impact on quality of life. 20 , 21 However, patients with painful SFN have a significant unmet need due to a lack of specifically approved treatments. Current treatments for painful SFN are those approved for diabetic peripheral neuropathy 22 and are associated with significant safety and tolerability issues: gabapentinoids have adverse effects including sleepiness, dizziness, ataxia, oedema, and tremor; tricyclic antidepressants have anticholinergic effects and duloxetine often induces nausea and abdominal pain; and opioids and opiates may cause addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Adding vitamin C prophylactic supplementation could reduce the incidence of CRPS following stratifying fracture type surgeries [36]. Vitamin C deficiency is associated with Aβ-fiber dysfunction and sensory loss [37 ▪ ]. Deoxy-sphingolipids, oxidative stress, and vitamin C correlate with qualitative and quantitative patterns of small fiber dysfunction and degeneration [37 ▪ ].…”
Section: Vitamin Cmentioning
confidence: 99%
“…Vitamin C deficiency is associated with Aβ-fiber dysfunction and sensory loss [37 ▪ ]. Deoxy-sphingolipids, oxidative stress, and vitamin C correlate with qualitative and quantitative patterns of small fiber dysfunction and degeneration [37 ▪ ].…”
Section: Vitamin Cmentioning
confidence: 99%